Amino-modified Scholl-coupling mesoporous polymer for online solid-phase extraction of plant growth regulators from bean sprouts. (15th August 2020) - Hou, Shenghuai; Sun, Xiaowei; Chen, Lizong; Yin, Yanzhen; Ji, Wenhua
Highlights: Amino-modified Scholl-coupling mesoporous polymer (NH2 @SMPA) was synthesized. NH2 @SMPA exhibits multiple adsorption mechanisms for plant growth regulators. Online SPE-HPLC method was used for the analysis of plant growth regulators. Abstract: A new amino-modified Scholl-coupling mesoporous polymer (NH2 @SMPA)-online solid-phase extraction method, coupled with high-performance liquid chromatography (online SPE-HPLC) was established for the analysis of six plant growth regulators (PGRs) in bean sprouts. NH2 @SMPA was synthesized by acid-catalyzed deacetylation of acetylamino-Scholl-coupling mesoporous polymer (SMPA). The diversity of functional groups, such as aromatic, acetylamino, and NH2, was conducive to multiple binding interactions between NH2 @SMPA and PGRs. NH2 @SMPA exhibited superior extraction capability for PGRs, compared with SMPA and commercial adsorbents. The extraction conditions, including loading solvent, pH of loading solution, eluting solvent, and flow rates of loading and elution, were optimized. Under the optimized conditions, wide linear ranges (0.01–500 μg kg −1 ) and low detection limits (2.34–20.2 ng kg −1 ) were obtained. The recoveries were satisfactory, i.e., 86.0% to 109% with relative standard deviations ≤9.8% (n = 3). Finally, the online SPE-HPLC method was successfully used for determination of PGRs in bean sprouts.